2017
DOI: 10.1038/jp.2017.129
|View full text |Cite
|
Sign up to set email alerts
|

In vivo assessment of placental and brain volumes in growth-restricted fetuses with and without fetal Doppler changes using quantitative 3D MRI

Abstract: ObjectiveThe relationship between placental and fetal brain growth is poorly understood, and difficult to assess. The objective of this study was to interrogate placental and fetal brain growth in healthy pregnancies and those complicated by fetal growth restriction (FGR).Study DesignIn a prospective, observational study, pregnant women with normal pregnancies or pregnancies complicated by FGR underwent fetal MR imaging. Placental, global and regional brain volumes were calculated.Results114 women (79 controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 49 publications
5
35
1
Order By: Relevance
“…Our study is supported by our prior work investigating MRI-based placental perfusion deficits following the exposure to IUI [44]. Specifically, we used MRI to examine placental damage following IUI and found a significant decrease in capillary blood volume and velocity, suggestive of vascular damage and blood flow disruption [44,45,46]. We speculate that these effects may contribute to the formation of a clot, subsequently decreasing placental volume.…”
Section: Discussionsupporting
confidence: 78%
“…Our study is supported by our prior work investigating MRI-based placental perfusion deficits following the exposure to IUI [44]. Specifically, we used MRI to examine placental damage following IUI and found a significant decrease in capillary blood volume and velocity, suggestive of vascular damage and blood flow disruption [44,45,46]. We speculate that these effects may contribute to the formation of a clot, subsequently decreasing placental volume.…”
Section: Discussionsupporting
confidence: 78%
“…This technique has been applied widely to the fetal brain, and extensions of this technique, although made substantially more complicated by non‐rigid motion, are being used for other abdominal organs . For placenta size, shape, and thickness estimation, these techniques are likely to represent the best way to acquire data . 3D reconstruction of structural MRI data has already been shown to have potential in surgical planning for laser division in TTTS, and as imaging and reconstruction techniques improve is likely to play an increasingly important role.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…FGR can be challenging to diagnose as placental function cannot currently be directly measured. Surrogate markers, such as abnormal fetal growth trajectory or abnormal blood flow to the placenta, are used with varying success. At present, there is no treatment for FGR, or the associated condition pre‐eclampsia; however, trials are exploring several new therapeutic avenues, including sildenafil, esomeprazole, metformin, pravastatin, and vascular endothelial growth factor maternal gene therapy .…”
Section: Introductionmentioning
confidence: 99%
“…Three studies (Damodaram et al, 2010; Ohgiya et al, 2016; Andescavage et al, 2017) investigated placental morphometry measurements in a FGR population compared to healthy controls. Although different definitions of FGR have been used (see Table 2), they all showed significantly reduced placental volume in the FGR population compared to the healthy pregnant population.…”
Section: Clinical Relevance Of Antenatal and Postnatal Assessment Ofmentioning
confidence: 99%
“…Furthermore, Damodaram et al showed that the placental volume remained significantly smaller throughout gestation in the FGR group, and that a lower placental volume was also associated with the severity of the FGR (detailed information on the severity subgroups can be found in Table 2) (Damodaram et al, 2010). Finally, Andescavage et al described that the placental volume was significantly lower in a subgroup of the FGR-population with abnormal umbilical artery Doppler (Andescavage et al, 2017). Higher mean placental thickness, lower macroscopic placental surface area and increase in max placental thickness/placental volume (PT/PV) ratio, were placental morphometry parameters that were significantly associated with FGR (Damodaram et al, 2010; Ohgiya et al, 2016).…”
Section: Clinical Relevance Of Antenatal and Postnatal Assessment Ofmentioning
confidence: 99%